P-137 Benefits of a day case paracentesis service in an outpatient specialist palliative care setting. (19th November 2022) - Fradsham, Sarah; Robinson, Claire
Abstract : Background: The presence of ascites in people with life-limiting illnesses has been shown to have a significant impact on quality of life (Reinglas, Amjadi, Petrcich, et al., 2016. Can J Gastroenterol Hepatol. 2016:4680543) but is also associated with a limited prognosis in certain patient groups. In patients with cirrhosis and ascites the mortality at 2 years is around 50% (Reinglas, Amjadi, Petrcich, et al., 2016.), with the median survival of patients with malignant ascites being between 10 and 24 months (Jehn, Küpferling, Oskay-Özcelik et al, 2015. Support Care Cancer. 23: 2073). Drainage of ascites (paracentesis) has been shown to provide symptom benefit for patients (Ota, Schultz & Segaline, 2021. Am J Hosp Palliat Care. 38:1042), however, traditionally this has been performed in an acute inpatient setting. Day case paracentesis in patients with cirrhosis has been shown to be safe, reduces demands on in-patient beds and saves money (Wilkinson, Jones, Bassi, et al., 2017. Gut. 66:A86). These services are infrequent in palliative care settings despite the feasibility of it having previously been reported (Korpi, Salminen, Piili, et al., 2018. J Palliat Med. 21: 836). There is limited reported evidence of additional benefits to patients of day case paracenteses. Method: A day case paracentesis service was set up in a hospice setting. A retrospective analysis of outcomes of the service is currently underway. Specific outcomes include: frequency of advance care planning (ACP) discussions, engagement with other hospice services, actual place of death and responsiveness of the service. Results: Eighteen day case paracenteses were performed over ten months. Provisional data shows that of these patients a significant proportion went on to die in hospice or home settings. Over 80% of the patients had completed some ACP - either documentation of preferred priorities for care and death or decisions around resuscitation. Over 50% of patients engaged with other services in the hospice. Frequency of presentation to primary or secondary care for symptoms related to ascites was low in all patients. Conclusion: Our day case paracentesis service gives the opportunity to engage patients in ACP discussions, link in with other hospice services and looks to reduce the burden on primary and secondary care. Further qualitative evaluation looking at patients' experience is planned.